Guide to the lighting of licensed premises - Butcher, Ken (Society of Light and Lighting, 2011)
This guide offers advice on lighting in all types of premises where alcoholic beverages are sold for consumption, which may range from a busy city centre pub to the bar in a working men's club. It also covers the question of energy use - current regulations can nowadays put severe constraints on lighting. It is written in terms that require no specialist knowledge of lighting. It provides advice and assistance to all those who are concerned with the design, equipping, management and operation of licensed premises', i.e. premises in which alcoholic beverages are sold for consumption on the premises. --